The Impact of Reward and Punishment on the Extrinsic Motivation of Elementary School Students - Maya Dwi Kusumawati; Mohammad Fauziddin; Rizki Ananda (STAI Hubbulwathan Duri, 2023)
This research is driven by the provision of reward and punishment, which influences student psychology in increasing learning motivation. The purpose of this study was to describe the impact of reward and punishment on students' extrinsic motivation. The research used a qualitative descriptive method with the subject of the fourth grade’s homeroom teachers and three students at a state elementary school in Kumantan. Data was collected by observation, interviews and documentation. Triangulation was carried out through focus group discussions between researchers, homeroom teachers and students. The results of the research show that giving rewards and punishment has an impact on student development if it is done properly and appropriately. Rewards are given to instill good values, which is done by habituation and appreciation when doing positive things, but when the students do negative things, the teacher will provide appropriate punishment for them as this punishment aims to prevent students from repeating unacceptable actions. Based on the results of this study, it was concluded that the effectiveness of reward and punishment as an educational tool to get feedback from students will be gained if they are appropriately delivered.